EFFECTIVE STRATEGIES FOR TEACHING ENGLISH GRAMMAR IN SECONDARY SCHOOL CLASSROOMS - Umarova Iroda Ravshanovna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:This  article  explores  practical  and  engaging  strategies  for  teaching English  grammar  in  secondary  school  settings.  Grammar  is  a  key  part  of  learning English, but many students find it difficult or uninteresting. The article explains how teachers  can  make  grammar  lessons  more  meaningful  through  the  use  of  real-life examples, interactive activities, storytelling, and visual materials. It also emphasizes the importance of clear explanations, student-centered methods, and regular practice. By  creating  a  positive  and  supportive  classroom  environment,  teachers  can  help learners build strong grammar skills and improve their communication in English.